Native Print Journalism in the United States: Dreams and Realities - Murphy, Sharon M. (Anthropologica, 2022)
This article examines the development of native American newspapers in the United States and traces their history for over 150 years. The contributions of pioneer native journalists, similarities and differences between early and contemporary native newspapers, and the problems faced by native journalists are discussed. The fluidity which has generally characterized the response of the native press to social and political influences is seen as a guarantee of its future vitality.